SYSTEM FOR DEVELOPMENT AND CONTROL OF LATENT IMAGES - Andrey A. Zharkikh; Galina V. Shagrova (Вестник Северо-Кавказского федерального университета)
This item presents the results of research into the methods employed for latent image development. The author proposes a definition for a system of latent image development and control, which comprises the features of all latent images.